The new developmental state and the challenges of the socio-ecological transformation: Lessons from Argentina and Brazil - Lucia Alfano (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2022)
The climate crisis is inevitably looming over the horizon. Some countries are much more vulnerable than others to its harshest consequences due to their existing issues of poverty and underdevelopment. At the same time, developmental policies pursue economic growth at the cost of environmental degradation and overexploitation. This contribution focuses on the actor that is called to find a balance between the necessity to address climate change and to reach economic prosperity, namely the state, in the specific configuration of the New Developmental State. The paper explores its role and capacity to set in motion a fundamental socio-ecological transformation with the goal of harmonising the conflicting spheres of sustainable development. From a theoretical point of view, the examination is conclusive in demonstrating that the new developmental state possesses the characteristic to be a driver of socio-ecological change. In practice, the trade-off between developmental and socioecological priorities is yet to be resolved.
Keywords: F63; F64; O11; O13; Q01; Q54; Q56; 330; Sustainable Development; New Developmental State; Socio-ecological transformation; Argentina; Brazil